Reconstructing the Death of Prophet Muhammad Through Hadith Criticism and Historical Analysis - Irfan Maulana Ahmad; Ahmad Musyafiq; Muhtarom Muhtarom; Achmad Azis Abidin (Jurnal Ulunnuha, 2026)
This study examines the hadiths describing the final moments of the Prophet Muhammad’s (SAW) life through the application of isnād (chain) and matn (text) criticism, with particular focus on the differing narrations transmitted by ‘Ā’ishah bint Abī Bakr and ‘Alī ibn Abī Ṭālib. The research specifically aims to determine how matn criticism can be used to evaluate the historical reliability and interpretive implications of these narrations concerning the Prophet’s final moments. Employing a qualitative library-based approach and descriptive-comparative analysis, the study examines narrations found in Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Ṭabaqāt Ibn Sa‘d, and Durrah an-Nāṣiḥīn fī al-Wa‘ẓ wa al-Irshād, alongside theoretical perspectives from Dirāsāt fī al-Ḥadīth wa al-Tārīkh and Manhaj Kritik Matan ‘Ā’isyah RA. The analysis evaluates the continuity of transmission, reliability of narrators, textual consistency with the Qur’an and authentic hadiths, and the historical coherence of each narration. The findings reveal that the narration transmitted by ‘Ā’ishah bint Abī Bakr regarding the Prophet’s passing in her embrace is the strongest and most historically reliable narration, classified as ṣaḥīḥ li dhātihi. In contrast, narrations attributed to ‘Alī ibn Abī Ṭālib and Ibn ‘Abbās are categorized as weak (ḍa‘īf) or disconnected (maqṭū‘) due to deficiencies in transmission, although they continue to hold spiritual and moral significance. The study concludes that matn criticism plays a crucial role in distinguishing between historically authoritative reports and narrations functioning primarily as moral or devotional traditions, thereby contributing to a more objective understanding of the Prophet Muhammad’s (SAW) death.